Repeated Massage Improves Swimmers’ Perceptions during Training Sessions but Not Sprint and Functional Performance: A Randomized Controlled Trial - Carvalho, Flávia A. [UNESP]; Batista, Natanael P. [UNESP]; Diniz, Fernanda P. [UNESP]; Machado, Aryane F. [UNESP]; Micheletti, Jéssica K. [UNESP]; Pastre, Carlos M. [UNESP] (MDPI, 2023)
This study aimed to investigate the effects of repeated massage adjusted for swimmers’ training on the perceptive, functional, and performance outcomes of a sprint. We also investigated the effects of a single short massage on swimmers’ self-reported perceptions after resistance training. This cross-over randomized controlled trial with concealed allocation, assessor blinding, and intention-to-treat analysis included 19 male and female competitive swimmers between 12 and 20 years old. Participants were subjected to three 12-min interventions over a week between resistance and swim training and monitored regarding training load and perceptions. After the intervention week we assessed: perceptive (well-being, heaviness, tiredness, discomfort, and pain), performance (sprint time, FINA points, and stroke characteristics), and functional outcomes (flexibility, squat jump, bench press, proprioception), in addition to athlete beliefs and preferences. A massage was defined as consisting of sliding movements on the arms, back, and anterior thigh, with metronomic rhythm control (1:1), and was divided into two protocols: superficial massage (SM) (light touch) and deep massage (DM) (light, moderate, intense effleurage) while the control (CON) rested. After repeated massage (SM and SM), participants had less chances to report tiredness, and they also maintained perceptions of well-being while CON got worse throughout the week. However, we found evidence of worsening of the perceptions of heaviness and pain at the main stages of the swim training for the massage groups. SM and DM had no effects over sprint and functional performance. Our results suggest that the swimmers were able to train harder with no harm to recovery.
Keywords: massage therapy; muscle soreness; recovery; swimming